Determinants of Child Marriage Using Ecological Theory: A Literature Review - Putri, Nike Dwi; Achmad, Harun; Pulubuhu, Dwia Aries Tina (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Indonesia is one of the ten countries with the highest prevalence of child marriage in the world. Efforts to prevent the practice of child marriage can be done through intervention on the determinants of child marriage. This article aims to examine and explain the factors that influence child marriage referring to ecological theory. The research method used is a literature review. Article searches were conducted on online journal databases found in Pubmed, Proquest, ScienceDirect, and Willey Online Library with the keyword "determinants of child marriage" and published in 2017-2021. The search results of articles discussing the determinants of child marriage found 13 articles that matched the inclusion criteria. The results of the article examination found that individual education and knowledge factors were part of the microsystem, household welfare factors and the attachment of children's relationships with parents were part of the mesosystem, rural living environment factors, social, cultural, and religious norms as an exosystem, and security factors. state, and regulations or laws as part of the macrosystem. The conclusion obtained is that the problem of child marriage is a multidimensional problem including individual, family, community, and state factors.